Nexus between foreign remittances and poverty alleviation: Empirical investigation of Tajikistan from Central Asia - Farrukh Nawaz; Umar Kayani; Ahmet Faruk Aysan (Cogent Social Sciences, 2024)
Remittances have become an increasingly important source of external financing for the low-income countries of Central Asia. The impact of Foreign remittances upon poverty alleviation has received substantial importance in academic writings, but very few studies have investigated the Central Asian region. Tajikistan was one of the poorest state of the former Soviet Republics, and it was further devastated by the twin shocks of the post-Soviet transition in 1991 and the civil war from to 1992–1997. The labors of Tajikistan mainly migrate to Russia and other countries of Central Asia for earning their livelihoods. The remittances from Russia to Tajikistan amounted to approximately $ 2.5 Billion in 2019 (accounting for 33% of their GDP). In this study we explored the impact of remittances on poverty alleviation of Tajikistan by taking the data for the variables like remittances, poverty size, capital formation, Per Capita GDP, inflation, and unemployment. We took the data from the World Development Bank Indicators for the time period 2010–2019. Initially, we ran the diagnostic tests including the unit root test for stationarity, the Pearson correlation test for multicollinearity, the Bruesch-Pagan/Cook-Weisberg test for heteroscedasticity, and the Wooldridge test for autocorrelation. After running the diagnostic test we applied the gowth-poverty model for gauging the relationship between the remittances and the poverty and we found a significant negative relationship between foreign remittances and poverty alleviation in case of Tajikistan.